(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This research has a general objective 1) To study the situation and operations of the Coronavirus Disease 2019 (COVID -19) outbreak abroad and domestically. And specific objectives 2) To study surveillance patterns, Prevent and control the spread of Coronavirus Disease 2019 (COVID -19) In Samut Prakan Provincial Central Prison 3) To make policy recommendations for the development of surveillance models and guidelines, Prevent and control the spread of Coronavirus Disease 2019 (COVID -19) In Samut Prakan Central Prison. It's qualitative research. The tools used in the research are documentary research data collection, in-depth interviews from 11 key contributors. Using semi-structured interviews and focus group discussions of 8 people. The results showed that 1) Coronavirus Disease 2019 Pandemic Situation It affects inmates in prisons both in Thailand and abroad. Prisons abroad have imposed measures to reduce overcrowding of inmates by temporarily releasing vulnerable inmates such as the elderly, Persons with underlying medical conditions and pregnant women and inmates who are on trial at court, Inmates are vaccinated, and preventive measures are taken by staff to reduce transmission. Meanwhile, prison operations in Thailand have been implemented in accordance with coronavirus surveillance measures. 2019 Strictly with new inmate care (upstream) Former inmates (midstream) and inmates released (downstream) 2) Surveillance model, Prevent and control the spread of Coronavirus Disease 2019 (COVID-19) in Samut Prakan Central Prison in accordance with the management guidelines "4 M". Starting from the management side, focusing on participatory management, especially with the host hospital, Bang Bo Hospital with good relationships for a long time. Determine the indicators, directs clear operations from inner prisons to other prisons, Adopt bubble & seal principles during the pandemic. Emphasis is placed on vaccine coverage among all staff and inmates. The budget is supported by several of the most important sources of budget: public donations. Personnel: Healthcare workers of prisons and host hospitals, such as: Bang Bo Hospital is very cooperative and helpful. Prison volunteers helped operate. Equipment, Material Side: Aid supplies are managed jointly through the support of host hospitals and between prisons. And 3) important policy recommendations should be managed by continuing to expand the management policy. The management should apply Buddhist management principles to the implementation of disease control surveillance. Manage resources, especially budgets from local government organizations, support increased operations, and develop the necessary medical supplies database model to be ready for use in emergencies.